Evaluation of the performance of different nano-ceramic tool grades when machining nickel-base, inconel 718, alloy - Ezugwu,E. O. (2004)
High-speed machining of aerospace alloys can be enhanced by the use of advanced cutting tool materials such as nano-grain size ceramics that exhibit improved physical and mechanical properties than their micron grain counterparts. The performance of recently developed nano-grain size ceramic tool materials were evaluated when machining nickel base, Inconel 718, in terms of tool life, tool failure modes and wear mechanisms as well as component forces generated under different roughing conditions. The tools were rejected mainly due to wear on the tool nose. It is also evident that chemical compositions of the tool materials played significant role in their failure. The alumina base ceramics performed better than the silicon nitride base ceramics. Severe abrasion wear was observed on both rake and flank faces of the cutting tools while cutting forces increased with increasing cutting speed when machining with the silicon nitride base nano-ceramic tools. This is probably due to the lower superplastic flow temperature of the nitride base nano-ceramics. The alumina base ceramics are more susceptible to chipping at the cutting edge than the silicon nitride base ceramics despite their higher edge toughness.